2020
DOI: 10.1088/1674-1056/ab90e8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation mechanism of catalyst structure on diamond crystal morphology under HPHT process*

Abstract: To elucidate the regulation mechanism of catalyst geometry structure to diamond growth, we establish three catalyst modes with different structures. The simulation results show that with the decrease of the protruding height of the catalyst, the low-temperature region gradually moves toward the center of the catalyst, which causes the distribution characteristics of the temperature and convection field in the catalyst to change. The temperature difference in vertical direction of the catalyst decreases gradual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…It has been suggested that diamond nucleation is more likely to occur with carbon nanoparticles containing amorphous carbon as a precursor, [46][47][48][49] and that the quantity of nucleation and granularity of synthesized nanodiamonds decrease with increasing crystallinity of the graphite precursor. [50][51][52][53] Thus, the decreasing average grain size of samples N1-N3 with increasing carbonization time may be attributed to the increase of crystallinity of carbon intermediates, which does not favor the nucleation and growth of nanodiamonds. The average grain size of sample N4 is slightly larger than that of sample N3.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that diamond nucleation is more likely to occur with carbon nanoparticles containing amorphous carbon as a precursor, [46][47][48][49] and that the quantity of nucleation and granularity of synthesized nanodiamonds decrease with increasing crystallinity of the graphite precursor. [50][51][52][53] Thus, the decreasing average grain size of samples N1-N3 with increasing carbonization time may be attributed to the increase of crystallinity of carbon intermediates, which does not favor the nucleation and growth of nanodiamonds. The average grain size of sample N4 is slightly larger than that of sample N3.…”
Section: Resultsmentioning
confidence: 99%
“…The diamond used in the experiment was purchased from ElementSix with a size of 1.5 mm×1.5 mm×1 mm, nitrogen content is about 10 −4 . Polished surface of diamond (1.5 mm×1.5 mm) is the (100) surface, which is irradiated for 3 h under 10 MeV electron irradiation and then annealed for 2 h under 850 • C. [28][29][30][31][32][33] The NV color center concentration formed is about 10 −6 . The functions of magnetic gathering ring mainly include magnetic gathering and antiinterference, so it is appropriate to use soft magnetic material and it is required to have high permeability, low coercivity low loss, high resistivity and high saturation magnetic induction.…”
Section: Methods and Experimentsmentioning
confidence: 99%
“…Объемные кристаллы алмаза успешно выращивают методом HPHT при температурах 1400 ± 50 • C и давлениях порядка 5−6 GPa; в современных установках роста типа Cubic высокое гидростатическое давление обеспечивается шестью цилиндрами сверхвысокого давления [27][28][29]. Россия в лице компании " New Diamond Technology" (NDT) является мировым лидером в этой области [30,31] -в 2020 г. компания сообщила о синтезированных монокристаллах весом более 100 карат.…”
Section: теоретический анализ 1методы синтеза и легирование монокрист...unclassified